2020
DOI: 10.22336/rjo.2020.11
|View full text |Cite
|
Sign up to set email alerts
|

Complex reconstruction of the orbitofrontal regions using three regional flaps after orbital exenteration for the treatment of basal cell carcinoma

Abstract: Objective. The current paper presents an interesting case of facial reconstruction after the excision of a giant basal cell carcinoma located in the orbitofrontal region. Methods. Performing the excision while securing the appropriate oncologic safety margin has determined the appearance of a soft tissue defect that required a complex reconstruction using three regional flaps: frontal, temporal fascial and temporal muscle flaps. Results. After the excision and reconstruction in a single surgical stage, the pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…These flaps have a dependable blood supply, large degree of rotation, and minimal donor site morbidity. Multiple studies have demonstrated the TPFF as a reliable flap for reconstructing an exenterated cavity [1,5] . For larger resections involving significant surrounding soft tissue, especially in the setting of periorbital skin cancers, free tissue transfer is often necessary for adequate reconstruction.…”
Section: Isolated Orbital Exenterationmentioning
confidence: 99%
“…These flaps have a dependable blood supply, large degree of rotation, and minimal donor site morbidity. Multiple studies have demonstrated the TPFF as a reliable flap for reconstructing an exenterated cavity [1,5] . For larger resections involving significant surrounding soft tissue, especially in the setting of periorbital skin cancers, free tissue transfer is often necessary for adequate reconstruction.…”
Section: Isolated Orbital Exenterationmentioning
confidence: 99%
“…Generally, eyelid reconstruction must respect two principles: first and foremost, the functional principle, of protecting the eye, and secondly, the aesthetic principle [ 4 ]. The upper eyelid must be mobile, dynamic, in order to ease the sight and eye opening and, at the same time, to ease closing the eye and protect the cornea.…”
Section: Introductionmentioning
confidence: 99%